A review of porous evaporative cooling for the preservation of fruits and vegetables. (2009)
The review of a porous evaporative cooler for the preservation of fruits and vegetables are reported in this paper. The different types of evaporative cooler designs under review include: pot-in-pot, cabinet, static, and charcoal cooling chambers. The gap between them is either filled with a jute, damp cloth, or sand. Water is linked to the cooler at the top, thus keeping the chamber cooled. The result of transient performance of the cooler revealed a depression in temperature in the storage chamber. Thus, the evaporative cooler has prospect for use for short term preservation of vegetables and fruits soon after harvest.